Risk factors and outcome for colistin-resistant Acinetobacter nosocomialis bacteraemia in patients without previous colistin exposure. (August 2015) - Wang, Y.-C.; Lee, Y.-T.; Yang, Y.-S.; Chen, C.-T.; Chiu, C.-H.; Yin, T.; Kuo, S.-C.; Chen, T.-L.; Lin, J.-C.; Wang, F.-D.; Fung, C.-P.; Chang, F.-Y.
Abstract: The clinical characteristics of patients with colistin-resistant Acinetobacter baumannii bacteraemia have been documented, but those of patients with bacteraemia caused by other Acinetobacter species remain unknown. Previous exposure to colistin has been shown to be associated with the emergence of colistin resistance, but may be not the only predisposing factor. In the current study, we highlight the risk and outcome of patients without previous exposure to colistin who acquired colistin-resistant Acinetobacter nosocomialis (ColRAN) bacteraemia. This 11-year single-centre retrospective study analysed 58 patients with ColRAN bacteraemia and 213 patients with colistin-susceptible A. nosocomialis (ColSAN) bacteraemia. Antimicrobial susceptibilities were determined with an agar dilution method. The clonal relationship of ColRAN isolates was determined with pulsed-field gel electrophoresis. A conjugation mating-out assay was conducted to delineate the potential transfer of colistin resistance genes. Multivariable analysis was performed to evaluate the risk factors for ColRAN bacteraemia. Chronic obstructive pulmonary disease (COPD) was independently associated with ColRAN bacteraemia (OR 3.04; 95% CI 1.45–6.37; p 0.003). Patients with ColRAN bacteraemia had higher APACHE II scores, but the two groups showed no significant differences in 14-day mortality (10.3% vs. 10.3%) or 28-day mortality (15.5% vs. 15.0%). ColRAN isolates had greater resistance than ColSAN isolates to all antimicrobial agents except for ciprofloxacin (0% vs. 6.6%). There were 16 different ColRAN pulsotypes, and two major clones were found. Colistin resistance did not transfer to colistin-susceptible A. baumannii or A. nosocomialis . These results show that COPD is an independent risk factor for acquisition of ColRAN bacteraemia. The mortality rates were similar between patients with ColRAN and ColSAN bacteraemia.